Method for preparing MOF-fiber composite material by growing MOF in-situ on fiber and application thereof

CN122999159APending Publication Date: 2026-10-30SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611426888.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]有鉴于现有技术的上述缺陷,本发明提出一种MOF-纤维复合材料的精准复合制备技术,该技术通过构建常压开放式回流条件下MOF在纤维基底表面的原位生长工艺,解决了传统MOF材料难加工、难成型、难规模制备的问题,实现了高性能MOF材料与成熟纤维加工体系的有效精准结合

Benefits of technology

[0032]本发明采用常压开放式回流反应体系替代传统高压水热/溶剂热方法,无需依赖高压反应釜等特殊设备,制备过程在常规加热条件下即可完成,显著降低了设备投入和生产复杂度。同时,该方法反应条件温和,可避免高温高压环境对聚丙烯(PP)、聚酯(PET)、纤维素等柔性基材造成结构损伤,有利于实现柔性功能材料的大面积制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999159A_ABST
    Figure CN122999159A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing MOF-fiber composite materials by in-situ growth of MOF on fibers and application thereof. The method utilizes the interface coordination induction effect between the surface active sites of the fiber substrate and metal ions, and realizes the uniform in-situ controllable growth and compounding of MOF crystals on the fiber surface by modulating the thermodynamic regulation of the nucleation kinetics, growth rate and crystal size evolution process of MOF materials. The method does not require complex equipment, can realize the in-situ growth and compounding of different types of MOF materials on various natural fibers, polymer fibers and inorganic fibers, and the obtained composite material has the flexibility of fiber materials and the high porosity and adjustable function of MOF materials. Based on the MOF-fiber composite material, it can be further applied to the fields of gas adsorption and separation, pollutant removal, photocatalysis, biological protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional fiber material preparation technology, and particularly relates to a synthesis method for preparing MOF-fiber composite materials by in-situ growth of MOF fibers and its bio-environmentally friendly applications. Background Technology

[0002] With the rapid development of public health and safety, indoor air quality improvement, environmental protection, and green manufacturing, functional fiber materials that combine air purification, biosafety protection, and environmental friendliness have attracted widespread attention. Fibers and textiles, due to their advantages such as light weight, flexibility, excellent breathability, large specific surface area, and ease of processing, are widely used in air filtration, personal protective equipment (PPE), smart textiles, biomedicine, and environmental remediation. Among these applications, volatile organic compounds (VOCs) and toxic and harmful gases remaining in materials used in indoor office and home decoration, as well as in transportation vehicles such as automotive interiors, pose long-term and continuous health risks. Furthermore, in public health emergencies, industrial production, and special work environments, PPE not only needs to effectively block particulate matter and pathogens but also needs to provide air purification and protection against harmful gases. Therefore, developing new fiber materials that combine multiple functions, such as indoor VOC adsorption and air purification, and active protection against outdoor PPE, has become an important development direction in the fields of air purification and health protection.

[0003] Currently, most traditional filter materials and PPEs use polymer fibers such as polypropylene (PP) and polyethylene terephthalate (PET) as a base, relying primarily on physical filtration mechanisms to intercept particulate matter. Their active adsorption capacity for VOCs and toxic gases is limited, and they lack continuous purification, self-cleaning, and multi-functional synergistic protection capabilities. As people's demands for health protection and air quality continue to increase, single physical filter materials are no longer sufficient to meet the needs of various applications, including indoor air purification and personal protection. Therefore, developing multi-functional fiber composite materials that combine high-efficiency adsorption, environmental purification, and long-term stability is of great significance for promoting the development of next-generation air filter materials and high-performance PPEs.

[0004] In recent years, porous adsorbent materials, photocatalytic materials, and interfacial catalytic materials have been widely studied in the fields of air purification and environmental governance due to their advantages such as being green, efficient, low-energy, and recyclable. Among them, porous materials can efficiently adsorb VOCs, toxic and harmful gases, and other air pollutants by relying on their abundant pore structure and ultra-high specific surface area; catalytic functional materials can further realize functions such as pollutant degradation, self-cleaning of material surfaces, and continuous purification. Therefore, integrating multiple functions such as adsorption, catalysis, and protection into fiber materials is an important technical approach to achieve the synergistic application of indoor air purification and outdoor personal protection.

[0005] Metal-organic frameworks (MOFs) are a class of novel porous crystalline materials formed by the coordination of metal ions or metal clusters with organic ligands. They possess ultra-high specific surface area, rich and tunable pore structures, excellent structural designability, and functional controllability. By controlling the composition of metal nodes, organic ligands, and functional groups, MOF materials can not only efficiently adsorb VOCs such as benzene, toluene, and formaldehyde, as well as other toxic and harmful gases, but also be endowed with multiple functions such as catalysis, self-cleaning, and biosafety protection. Therefore, they have broad application prospects in air purification, environmental remediation, and high-performance PPE. Furthermore, MOFs can be grown in situ on various substrates such as fibers, fabrics, porous membranes, and carbon materials, forming MOF-fiber composite materials that combine the flexibility of fibers with the adsorption and catalytic functions of MOFs, providing a new technical route for the development of next-generation functional fibers.

[0006] However, most current preparations of MOF-fiber composites employ closed solvothermal or hydrothermal methods, requiring closed equipment such as high-pressure reactors to grow MOF crystals under high temperature and pressure conditions. These methods are not only costly and complex, but also pose certain safety risks, hindering continuous and large-scale production. Furthermore, the high-temperature and high-pressure reaction conditions place high demands on the heat resistance and dimensional stability of commonly used PPE fiber substrates such as polypropylene (PP) and polyethylene terephthalate (PET), limiting the widespread application of MOF materials in large-area flexible fiber materials. In addition, existing methods generally suffer from limited applicability to various fiber substrates, insufficient MOF loading uniformity, weak interfacial coordination bonding, and insufficient process versatility, making it difficult to simultaneously meet the dual performance and preparation process requirements of both indoor air purification materials and outdoor PPE materials.

[0007] Traditional closed solvothermal systems rely on a fixed-volume reaction space, making it difficult to achieve large-area continuous processing of fiber substrates. This invention proposes a method for in-situ loading of MOFs onto fibers at ambient pressure and low temperature using an open reflux reaction apparatus. Through open solvent circulation and a mild crystallization environment, MOF materials can be grown in situ at low pressure and ambient temperature, with simple activation and continuous operation. This method should be simple, safe, reliable, require no high-pressure reaction equipment, be easy to operate, and suitable for continuous and large-scale production. Simultaneously, it should maintain the original flexibility, breathability, and mechanical properties of the fiber material, and endow it with multiple application functions such as efficient VOC adsorption, air purification, and personal protective equipment (PPE). This provides a new technical solution for the industrial-scale preparation of MOF functional fibers and their widespread application in indoor air purification and outdoor health protection. Summary of the Invention

[0008] In view of the above-mentioned deficiencies of the prior art, the present invention proposes a precise composite preparation technology for MOF-fiber composite materials. This technology solves the problems of difficult processing, difficult forming, and difficult large-scale preparation of traditional MOF materials by constructing an in-situ growth process of MOF on the surface of fiber substrate under normal pressure open reflux conditions, and realizes the effective and precise combination of high-performance MOF materials and mature fiber processing system.

[0009] To achieve the above objectives, in a first aspect, the present invention provides a method for synthesizing MOF-fiber composite materials, comprising the following steps: (1) Fiber pretreatment: The fiber substrate is pretreated under the action of modulator to form an interfacial coordination environment on the fiber surface that is conducive to the nucleation and growth of MOF crystals; (2) Preparation of reaction system: Add the metal ion source and organic ligand to the reaction system containing solvent and modifier, and mix evenly; (3) In-situ growth: The pretreated fiber substrate is brought into contact with the reaction system obtained in step (2), and heated and crystallized under normal pressure open reflux conditions, so that metal ions and organic ligands coordinate and assemble on the fiber surface, thereby realizing the in-situ growth of MOF crystals on the fiber substrate. (4) Post-treatment: The composite material obtained in step (3) is washed, dried and activated to obtain MOF-fiber composite material.

[0010] In some embodiments, in step (3), the atmospheric pressure open reflux condition utilizes the solvent evaporation-condensation cycle in an open environment to maintain a stable reaction environment without the need for high-pressure equipment, thereby enabling continuous nucleation and growth of MOF crystals.

[0011] The method describes a synergistic process of "fiber interface-induced nucleation - solution coordination assembly - continuous crystal growth" to achieve the transformation of MOF from free nucleation in solution to directional growth on the fiber surface. Polar functional groups or active sites on the fiber substrate surface serve as heterogeneous nucleation centers, increasing the probability of crystal nucleus formation on the fiber surface through interfacial coordination with metal ions. Modulators regulate the release rate of metal ions, the deprotonation process of organic ligands, and the free energy of crystal nucleus formation, controlling the crystal size, growth rate, and spatial distribution. The more modulators, the smaller the crystal size, while different types of modulators affect the nucleation rate and thus the spatial distribution. In an atmospheric pressure reflux system, stable reaction conditions are maintained through continuous solvent circulation, enabling the MOF material to grow uniformly on the fiber surface and form a stable bonding layer.

[0012] In some embodiments, the metal ion source is selected from metal ions and transition metal ions.

[0013] In a preferred embodiment, the metal ion source is selected from zirconium ions (Zr). 4+ ), hafnium ions (Hf) 4+ ), cerium ions (Ce) 4+ ), titanium ions (Ti 4+ ), iron ions (Fe 3+ ), aluminum ions (Al) 3+ ), copper ions (Cu) 2+ ), zinc ions (Zn 2+ At least one of the following, wherein the metal ion source is selected from at least one of metal chloride, metal oxychloride, metal nitrate, and metal acetate.

[0014] In some embodiments, the organic ligand is at least one of carboxylic acids with or without aromatic rings, nitrogen-containing heterocyclic compounds, phosphoric acids, phenolic hydroxyl compounds, sulfur-containing ligands, and functional ligands.

[0015] In a preferred embodiment, the organic ligand is selected from at least one of the following: terephthalic acid, trimellitic acid, 1,3,5-tris(4-carboxyphenyl)benzene, fumaric acid, ethylenediaminetetraacetic acid, etc.; or 2-methylimidazolium, imidazolium, 1,2,4-triazole, 4,4'-bipyridine, terpyridine, etc.; or phenylphosphonic acid, catechol, tetrahydroxybenzene, dithiocarbamate, thiophene, etc.; or functionalized terephthalic acid, functionalized trimellitic acid, functionalized phenylphosphonic acid, porphyrin, etc. The structural formulas of the above organic ligands are as follows: .

[0016] In some embodiments, the modulator is selected from regulators known in the art that can be used to control the growth of MOF crystals, including but not limited to one or more organic acids and inorganic acids.

[0017] In a preferred embodiment, the modifier is selected from at least one of trifluoroacetic acid, acetic acid, formic acid, propionic acid, butyric acid, benzoic acid, sulfonic acid, citric acid, oxalic acid, hydrochloric acid, nitric acid, and phosphoric acid. The structural formulas of the above modifiers are as follows: .

[0018] In some embodiments, the molar ratio of the metal salt:ligand:modifier is 1:1.5:20.

[0019] In some embodiments, the fiber substrate is selected from at least one of natural fibers, polymer fibers, inorganic fibers, carbon-based fibers, or conductive fibers.

[0020] In a preferred embodiment, the fiber substrate is selected from at least one of polypropylene (PP), polyethylene terephthalate (PET), polyamide (PA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polylactic acid (PLA), polyacrylonitrile (PAN), cotton fiber, hemp fiber, silk, carbon fiber, carbon cloth, carbon paper, glass fiber, and electrospun nanofiber membranes. The structural formulas of the above fiber substrates are as follows: .

[0021] In some embodiments, the solvent in step (2) is selected from at least one of N,N-dimethylformamide (DMF), deionized water, ethanol, and methanol; and the detergent used in step (4) is selected from at least one of methanol, ethanol, acetone, and deionized water.

[0022] In some embodiments, in step (3), the reaction temperature is 60-180 °C and the reflux time is 4-12 hours.

[0023] In some embodiments, in step (4), the drying and activation conditions are to treat under vacuum conditions at 80-150 °C for 6-48 hours.

[0024] In a preferred embodiment, the drying and activation conditions are as follows: activation at 120 °C under vacuum for 24 hours.

[0025] In a second aspect, the present invention also provides MOF-fiber composite materials prepared according to the above method.

[0026] In some embodiments, in the MOF-fiber composite material, MOF crystals are uniformly loaded onto the surface of the fiber substrate through chemical bonding to form a stable interfacial bonding layer.

[0027] In a third aspect, the present invention also provides the application of the MOF-fiber composite material in the fields of air purification, personal protective equipment, environmental remediation or biosafety protection.

[0028] In some embodiments, the applications include: (1) applications in the adsorption of volatile organic pollutants; (2) applications in the catalytic degradation of pollutants by visible light; (3) applications in the catalytic antiviral activity by visible light; and (4) applications in the preparation of protective masks, protective clothing, air filter materials or fresh air system filter materials.

[0029] In some embodiments, the MOF-fiber composite material prepared by the above method is used in the fields of environmental remediation and bioprotection: (1) In the adsorption of volatile organic pollutants (VOCs), MOF-fiber composite material is placed in a VOCs-containing gas environment, and the porous structure of MOF material is used to achieve the adsorption and removal of pollutants.

[0030] (2) In visible light catalytic antiviral applications, MOF-fiber composite materials are brought into contact with the virus-contaminated system and treated under visible light, specific wavelength light sources or simulated sunlight conditions to achieve virus inactivation.

[0031] Technical effect

[0032] This invention employs an atmospheric pressure open reflux reaction system to replace the traditional high-pressure hydrothermal / solvothermal method, eliminating the need for specialized equipment such as high-pressure reactors. The preparation process can be completed under conventional heating conditions, significantly reducing equipment investment and production complexity. Furthermore, the method provides mild reaction conditions, avoiding structural damage to flexible substrates such as polypropylene (PP), polyester (PET), and cellulose caused by high-temperature and high-pressure environments, thus facilitating the large-area preparation of flexible functional materials.

[0033] Furthermore, by adjusting the proportions of metal nodes, organic ligands, modulators, and reaction conditions, this invention can achieve in-situ construction of different types of MOF materials on different fiber substrates, exhibiting good process compatibility and material design freedom, and can be extended to the development of MOF fiber materials with different functional requirements.

[0034] The MOF-fiber composite material prepared by this invention combines the high specific surface area, high porosity structure and adjustable functional sites of MOF materials with the excellent flexibility, air permeability and processability of fiber materials, and can realize the functional upgrade of traditional fiber materials.

[0035] Taking Zr-UiO-66-NH2-meltblown nonwoven composite material as an example, this material exhibits excellent VOC adsorption performance. In pure benzene vapor at a pressure of 11.427 kPa, the adsorption capacity for benzene reaches 451.30 mg / g; in a formaldehyde-nitrogen mixture at 100 ppm, the adsorption capacity for formaldehyde reaches 9.82 mg / g, indicating that it has good application potential in the field of volatile organic pollutant (VOCs) removal.

[0036] Meanwhile, by introducing a MOF structure with photocatalytic activity, the fiber material can be further endowed with visible light response and active protection capabilities, realizing multi-functional integration such as pollutant adsorption, photocatalytic degradation and microbial inactivation, breaking through the functional limitations of traditional filter materials that rely solely on physical interception.

[0037] The raw materials involved in this invention (including metal salts, organic ligands, modifiers, and fiber substrates) are all mature chemicals and industrial materials, widely available, stably supplied, and suitable for continuous production. The preparation process mainly includes: fiber pretreatment; mixing of metal salts, organic ligands, and modifiers; in-situ growth under normal pressure reflux; and washing, drying, and activation treatments. These steps are all routine operations in the field of materials processing and can be easily scaled up using existing impregnation, coating, roll-to-roll processing, or continuous reaction equipment, thus achieving the transition from laboratory preparation to industrial production.

[0038] Compared to the traditional MOF powder production and subsequent compounding process, this invention reduces the steps of powder dispersion, binder introduction, and secondary processing, thereby lowering production costs and improving product stability and consistency.

[0039] The MOF-fiber composite material obtained by this invention has good application expansion capabilities. It can be adjusted according to the MOF structure and fiber type to achieve applications in different fields: (1) In the field of air purification, the rich pore structure and high adsorption capacity of MOF can be used for indoor air purification, fresh air filtration, industrial waste gas treatment and other fields to achieve efficient removal of harmful gases such as VOCs. (2) In the field of personal protection, based on mature protective material systems such as meltblown nonwoven fabric, new protective masks, protective clothing and filter materials with adsorption of pollutants and active antimicrobial functions can be developed to improve public health protection capabilities. (3) In the field of environmental governance, by constructing MOF fiber materials with photocatalytic properties, the synergistic effect of pollutant adsorption and photocatalytic degradation can be achieved, which is suitable for water treatment, air pollution control and green environmental protection materials. (4) In the field of high value-added functional materials, the highly designable characteristics of MOF structure can be further expanded to emerging application directions such as sensors, catalytic reaction carriers, and intelligent filter materials. The technology of this invention can upgrade traditional fiber materials into new composite materials with high value-added functions, which helps to promote the transformation of MOF materials from laboratory research to practical applications. Attached Figure Description

[0040] Figure 1 X-ray diffraction (XRD) spectra of different UiO-66 type MOF-meltblown nonwoven fiber composites; Figure 2 Scanning electron microscope (SEM) images of different UiO-66 type MOF-meltblown nonwoven fiber composites; Figure 3 Scanning electron microscope (SEM) image of blank meltblown nonwoven fibers; Figure 4 Scanning electron microscope (SEM) images of MOF-cotton fiber composites and MOF-carbon fiber composites; Figure 5 The UV-Vis absorption spectra of different UiO-66 type MOF-meltblown nonwoven fiber composites are shown. Figure 6 A comparison of the Fourier transform infrared (FT-IR) spectra of MOF-meltblown nonwoven fiber composite material and blank meltblown nonwoven fiber; Figure 7 The graph shows the mechanical property test results of MOF-meltblown nonwoven fiber composite material and blank meltblown nonwoven fiber. Figure 8 Figure 1 shows the contact angle test results of MOF-meltblown nonwoven fiber composites with different MOF loadings. Figure 9 This is a schematic diagram illustrating the visible light photocatalytic antiviral mechanism of MOF-fiber composite materials. Figure 10 This is a schematic diagram of the experimental procedure for visible light photocatalytic antiviral activity using MOF-fiber composite materials. Figure 11 The figure shows the test results of the antiviral performance of different MOF-meltblown nonwoven fiber composites under 405 nm visible light irradiation. Figure 12 The figure shows the test results of the adsorption performance of MOF-meltblown nonwoven fiber composite material for benzene and formaldehyde. Detailed Implementation

[0041] The present invention will be further described below with reference to specific embodiments. It should be noted that the following embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Adjustments to the material composition, reaction conditions, and process parameters made by those skilled in the art without departing from the technical concept of the present invention should all fall within the scope of protection of the present invention.

[0042] Example 1: Preparation of MOF-fiber composite material Zr-UiO-66-NH2

[0043] (1) Fiber pretreatment: The polypropylene fiber substrate is soaked in trifluoroacetic acid (CF3COOH) modulator to form an interfacial coordination environment on the fiber surface that is conducive to the nucleation and growth of MOF crystals. (2) Preparation of reaction system: Add 0.70 g zirconium tetrachloride (ZrCl4) and 0.81 g 2-aminoterephthalic acid (BDC-NH2) to the reaction system containing deionized water (H2O), N,N-dimethylformamide (DMF) and trifluoroacetic acid, and mix well; (3) In-situ growth: The pretreated fiber substrate is brought into contact with the reaction system obtained in step (2), and refluxed at 100 °C for 4 hours under normal pressure open reflux conditions to crystallize it, so that metal ions and organic ligands can coordinate and assemble on the fiber surface, thereby realizing the in-situ growth of MOF crystals on the fiber substrate. (4) Post-treatment: The composite material obtained in step (3) was washed with anhydrous ethanol (CH3CH2OH) and deionized water, dried under vacuum at 120 °C, and activated for 24 hours to obtain MOF-fiber composite material Zr-UiO-66-NH2.

[0044] Example 2: Preparation of MOF-fiber composite material Zr-UiO-66-COOH

[0045] Zr-UiO-66-COOH was prepared using the same method as in Example 1, except that the ligand 2-aminoterephthalic acid was replaced with an equimolar amount of 1,2,4-benzenetricarboxylic acid (BDC-COOH).

[0046] Example 3: Preparation of MOF-fiber composite material Zr-UiO-66-(COOH)2

[0047] Zr-UiO-66-(COOH)2 was prepared using the same method as in Example 1, except that the ligand 2-aminoterephthalic acid was replaced with an equimolar amount of 1,2,4,5-benzenetetracarboxylic acid (BDC-(COOH)2).

[0048] Example 4: Preparation of MOF-fiber composite material Zr-UiO-66-OH

[0049] Zr-UiO-66-OH was prepared using the same method as in Example 1, except that the ligand 2-aminoterephthalic acid was replaced with an equal amount of 2-hydroxyterephthalic acid (BDC-OH).

[0050] Example 5: Preparation of MOF-fiber composite material Zr-UiO-66-(OH)2

[0051] Zr-UiO-66-(OH)2 was prepared using the same method as in Example 1, except that the ligand 2-aminoterephthalic acid was replaced with an equal amount of 2,3-dihydroxyterephthalic acid or 2,5-dihydroxyterephthalic acid (BDC-(OH)2).

[0052] Example 6: Preparation of MOF-fiber composite material Zr-UiO-66-NO2

[0053] Zr-UiO-66-NO2 was prepared using the same method as in Example 1, except that the ligand 2-aminoterephthalic acid was replaced with an equal amount of 2-nitroterephthalic acid (BDC-NO2).

[0054] Experimental Example 1

[0055] The crystal structure of the MOF-fiber composite materials prepared in Examples 1-6 was analyzed using an X-ray diffractometer (Mini Flex 600 XRD). The test conditions were: Cu target radiation, tube voltage 40 kV, tube current 15 mA, and scanning range 2θ = 5°-50°.

[0056] Test results are as follows Figure 1 As shown, the different Zr-based MOF-fiber composites prepared all exhibit characteristic diffraction peaks corresponding to the UiO-66 standard structure at approximately 7.4° and 8.5° 2θ, indicating that MOF crystals were successfully grown and composited on the fiber substrate surface in situ, while maintaining the UiO-66 type topology.

[0057] Experimental Example 2

[0058] The morphology of the MOF-meltblown nonwoven fiber composites prepared in Examples 1-6 was observed using a scanning electron microscope (ZEISS Sigma 300).

[0059] The results are as follows Figure 2 As shown, compared with untreated meltblown nonwoven fibers ( Figure 3 In contrast, obvious MOF crystal particles were observed on the surface of all composite fibers, indicating that MOF crystals can grow in situ on the fiber surface. The size and distribution of MOF crystals formed by different functionalized ligands varied. Specifically, the MOF particles on the surface of Zr-UiO-66-NH2 and Zr-UiO-66-NO2 composites were smaller and more uniformly distributed; MOF materials containing multi-carboxyl or hydroxyl functionalized ligands exhibited varying degrees of crystal size variation.

[0060] Example 7 Preparation of UiO-66-NH2@Cotton Fiber

[0061] UiO-66-NH2@Cotton Fiber was prepared using the same method as in Example 1, except that the fiber-based polypropylene meltblown nonwoven fabric was replaced with cotton fabric.

[0062] Example 8 Preparation of UiO-66-NH2@Carbon Cloth

[0063] UiO-66-NH2@Carbon Cloth was prepared using the same method as in Example 1, except that the fiber-based polypropylene meltblown nonwoven fabric was replaced with carbon cloth.

[0064] Experimental Example 3

[0065] The MOF-cotton fiber composite material and MOF-carbon cloth composite material prepared in Examples 7 and 8 were characterized using a scanning electron microscope (ZEISS Sigma 300).

[0066] The results are as follows Figure 4 As shown, Zr-UiO-66-NH2 crystals can be uniformly loaded on the surface of cotton fiber and carbon cloth fiber, indicating that the method described in this invention is not only applicable to meltblown nonwoven fibers, but also applicable to different types of fiber substrates, realizing in-situ growth and composite of MOF materials.

[0067] Test Example 4

[0068] The light absorption properties of the MOF-meltblown nonwoven fiber composites prepared in Examples 1-6 in the range of 200-1000 nm were tested using a UV-Vis-NIR spectrophotometer (Shimadzu UV-3600i Plus).

[0069] The results are as follows Figure 5 As shown, the partially functionalized Zr-based MOF-fiber composites exhibit significant visible light absorption capabilities. Among them, the Zr-UiO-66-NH2, Zr-UiO-66-OH and Zr-UiO-66-(OH)2 composites have strong absorption responses in the 400-500 nm range, indicating that the obtained composites have visible light response capabilities.

[0070] Experimental Example 5

[0071] The MOF-meltblown nonwoven fiber composite material prepared in Example 1 was tested using Fourier transform infrared spectroscopy, with a test range of 600-4000 cm⁻¹. –1 And compared with untreated fibers.

[0072] The results are as follows Figure 6As shown, the Zr-UiO-66-NH2-meltblown nonwoven composite material exhibits characteristic absorption peaks originating from amino, carboxyl, C=O, and Zr–O coordination structures, while untreated fibers do not show the above characteristic signals, proving that the UiO-66-NH2 structure has been successfully introduced into the fiber substrate.

[0073] Experimental Example 6

[0074] The tensile strength and tensile modulus of the MOF-meltblown nonwoven fiber composites prepared in Examples 1-6 were tested using an electronic universal testing machine (Sansi Yongheng CMT5504).

[0075] The results are shown in Table 1 below. Figure 7 As shown, the horizontal axis represents tensile strength, and the vertical axis represents tensile modulus. Compared with unloaded MOF meltblown nonwoven fibers, MOF-fiber composites exhibit enhanced mechanical properties. Among them, the Zr-UiO-66-NH2 composite has higher tensile strength and tensile modulus, indicating that MOF crystal loading can improve the mechanical stability of fiber materials.

[0076] Table 1

[0077] Experimental Example 7

[0078] The surface contact angle and water absorption properties of Zr-UiO-66-NH2-meltblown nonwoven composites with different MOF loadings were tested using a contact angle tester (KRÜSS DSA100) and compared with those of untreated fibers.

[0079] The results are as follows Figure 8 As shown, with the increase of MOF loading, the surface wettability of the composite material changes, showing enhanced water absorption capacity, indicating that the MOF structure can regulate the surface properties of fiber materials.

[0080] Example 9: Application of MOF-fiber composite materials

[0081] The MOF-fiber composite material prepared by the above method can be used in the fields of environmental remediation and biological protection. (1) In the adsorption of volatile organic pollutants (VOCs), MOF-fiber composite material is placed in a VOCs-containing gas environment, and the porous structure of MOF material is used to achieve the adsorption and removal of pollutants.

[0082] (2) In the application of visible light catalytic antiviral treatment, MOF-fiber composite material is immersed in virus solution and treated under visible light, specific wavelength light source or simulated sunlight to achieve virus inactivation.

[0083] Experimental Example 8

[0084] like Figure 9 The diagram shows the photocatalytic antiviral activity of MOF-fiber composite materials. Figure 10 This is the antiviral testing process.

[0085] The antiviral performance of MOF-meltblown nonwoven fiber composite material was tested using the method described in Example 9. A 1mm... 2 The MOF-fiber composite material was mixed and contacted with the HSV-1 virus system, and then irradiated with a specific wavelength light source (405 nm as an example) for 2 hours before the fibers were removed. The treated virus system was added to a Vero cell culture system, and the antiviral performance of the material was evaluated by cell viability.

[0086] The results are as follows Figure 11 As shown, under 405 nm visible light irradiation, the Zr-UiO-66-NH2-meltblown nonwoven fiber composite material exhibited a cell survival rate of over 80% after 2 hours of irradiation, demonstrating a high virus inactivation ability and proving that the material has the potential for visible light photocatalytic antiviral applications.

[0087] Experimental Example 9

[0088] The MOF-meltblown nonwoven fiber composites prepared in Examples 1 and 5 were tested in a vacuum environment using a vacuum static gravimetric adsorption analyzer (BSD-VVS). Benzene vapor evaporated from liquid benzene in the reagent tube was introduced into the test chamber, and the benzene P / P0 ratio was controlled at a specified temperature of 25°C. -0.2-0.1-0.09-0.08-0.07-0.06-0.054-0.048-0.042-0.036-0.03-0.024-0.018-0.012-0.006, allowing the sample to adsorb, continuously acquiring time-weight data until adsorption equilibrium was reached, and testing the adsorption performance of benzene on the Zr-UiO-66-NH2 and Zr-UiO-66-(OH)2 composite materials; and testing the adsorption performance of formaldehyde by continuously introducing 100 ppm of formaldehyde / nitrogen mixture (volume ratio 0.01:99.99, total flow rate 0.8929 mmol / min) into the Zr-UiO-66-NH2 composite material.

[0089] The results are as follows Figure 12As shown, the Zr-UiO-66-NH2-meltblown nonwoven composite material exhibits high VOCs adsorption capacity, with a benzene adsorption capacity of 451.30 mg / g and a formaldehyde adsorption capacity of 9.82 mg / g; the Zr-UiO-66-(OH)2 composite material also exhibits good benzene adsorption performance, with an adsorption capacity of 259.84 mg / g.

[0090] The above results indicate that the MOF-fiber composite material prepared by this invention combines the porous structure of MOF with the processability of fiber materials, and has application value in the field of VOCs adsorption and environmental purification.

[0091] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Those skilled in the art can adjust or optimize the material composition, preparation conditions, and application methods according to actual needs without departing from the technical concept of the present invention, and all such adjustments should be included within the scope of protection of the present invention.

Claims

1. A method for synthesizing MOF-fiber composite materials, comprising the following steps: (1) Fiber pretreatment: The fiber substrate is pretreated under the action of modulator to form an interfacial coordination environment on the fiber surface that is conducive to the nucleation and growth of MOF crystals; (2) Preparation of reaction system: Add the metal ion source and organic ligand to the reaction system containing solvent and modifier, and mix evenly; (3) In-situ growth: The pretreated fiber substrate is brought into contact with the reaction system obtained in step (2), and heated and crystallized under normal pressure open reflux conditions, so that metal ions and organic ligands coordinate and assemble on the fiber surface, thereby realizing the in-situ growth of MOF crystals on the fiber substrate. (4) Post-treatment: The composite material obtained in step (3) is washed, dried and activated to obtain MOF-fiber composite material.

2. The synthesis method according to claim 1, wherein, The metal ion source is selected from at least one of zirconium ions, hafnium ions, cerium ions, titanium ions, iron ions, aluminum ions, copper ions, and zinc ions, and the metal ion source is selected from at least one of metal chlorides, metal oxychlorides, metal nitrates, and metal acetates.

3. The synthesis method according to claim 1, wherein, The organic ligand is at least one of the following: carboxylic acids with or without aromatic rings, nitrogen-containing heterocyclic compounds, phosphoric acids, phenolic hydroxyl compounds, sulfur-containing ligands, and functional ligands.

4. The synthesis method according to claim 3, wherein, The organic ligand is selected from at least one of terephthalic acid, pyromellitic acid, 1,3,5-tris(4-carboxyphenyl)benzene, fumaric acid, ethylenediaminetetraacetic acid, 2-methylimidazolium, imidazolium, 1,2,4-triazole, 4,4'-bipyridine, terpyridine, phenylphosphonic acid, catechol, tetrahydroxybenzene, dithiocarbamate, thiophene, functionalized terephthalic acid, functionalized pyromellitic acid, functionalized phenylphosphonic acid, and porphyrin.

5. The synthesis method according to claim 1, wherein, The modifier is selected from at least one of trifluoroacetic acid, acetic acid, formic acid, propionic acid, butyric acid, benzoic acid, sulfonic acid, citric acid, oxalic acid, hydrochloric acid, nitric acid, and phosphoric acid.

6. The synthesis method according to any one of claims 1-5, wherein, The molar ratio of the metal salt, ligand, and modulator is 1:1.5:

20.

7. The synthesis method according to claim 1, wherein, The fiber substrate is selected from at least one of natural fibers, polymer fibers, inorganic fibers, carbon-based fibers, or conductive fibers.

8. The synthesis method according to claim 7, wherein, At least one of the following must be met: a) The fiber substrate is selected from at least one of polypropylene, polyethylene terephthalate, polyamide, polyvinylidene fluoride, polytetrafluoroethylene, polylactic acid, polyacrylonitrile, cotton fiber, hemp fiber, silk, carbon fiber, carbon cloth, carbon paper, glass fiber, and electrospun nanofiber membrane. b) The solvent used in step (2) is selected from at least one of N,N-dimethylformamide, deionized water, ethanol, and methanol; the detergent used in step (4) is selected from at least one of methanol, ethanol, acetone, and deionized water. c) In step (3), the reaction temperature is 60-180 ℃ and the reflux time is 4-12 hours; d) In step (4), the drying and activation conditions are: treatment under vacuum at 80-150 °C for 6-48 hours; e) In step (4), the drying and activation conditions are: activation at 120 °C under vacuum for 24 hours.

9. The MOF-fiber composite material prepared by the synthesis method according to any one of claims 1-8.

10. The application of the MOF-fiber composite material according to claim 9 in the fields of air purification, personal protective equipment, environmental management or biosafety protection.